Combinatorial interactions of Serpent, Lozenge, and U-shaped regulate crystal cell lineage commitment during Drosophila hematopoiesis - Fossett, Nancy (National Academy of Sciences, 2003)
The GATA factor Serpent (Srp) is required for hemocyte precursor formation during Drosophila hematopoiesis. These blood cell progenitors give rise to two distinct lineages within the developing embryo. Lozenge, a Runx protein homologue, and Glial cells missing-1 and -2 are essential for crystal cell and plasmatocyte production, respectively. In contrast U-shaped, a Friend of GATA class factor, antagonizes crystal cell formation. Here we show that Srp, Lozenge, and U-shaped interact in different combinations to regulate crystal cell lineage commitment. Coexpression of Srp and Lozenge synergistically activated the crystal cell program in both embryonic and larval stages. Furthermore, expression of Lozenge and SrpNC, a Srp isoform with N- and C-terminal zinc fingers, inhibited u-shaped expression, indicating that crystal cell activation coincided with the down-regulation of this repressor-encoding gene. In contrast, whereas U-shaped and SrpNC together blocked crystal cell production, coexpression of U-shaped with noninteracting Srp proteins failed to prevent overproduction of this hemocyte population. Such results indicated that U-shaped and SrpNC must interact to block crystal cell production. Taken together, these studies show that the specialized SrpNC isoform plays a pivotal role during crystal cell lineage commitment, acting as an activator or repressor depending on the availability of specific transcriptional coregulators. These findings provide definitive proof of the combinatorial regulation of hematopoiesis in Drosophila and an in vivo demonstration of GATA and Runx functional interaction in a blood cell commitment program.